Electrode, secondary battery, battery pack, and vehicle
Patent Information
- Application Number
- CN202610233592.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-17
- Filing Date
- 2026-02-27
- Publication Date
- 2026-10-23
AI Technical Summary
[0008]根据上述构成的电极,能够提供可提供电池制造的成品率高且倍率性能高的二次电池的电极、倍率性能高的二次电池及电池包、以及具备该电池包的车辆。
Smart Images

Figure CN122968236A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present invention relate to electrodes, secondary batteries, battery packs, and vehicles. Background Technology
[0002] Lithium-ion batteries, which charge and discharge by moving lithium ions between the negative and positive electrodes, such as non-aqueous electrolyte batteries, are being actively researched as high-energy-density batteries.
[0003] In typical electrodes of secondary batteries such as lithium-ion batteries, in addition to electrode active materials that facilitate charging and discharging through lithium-ion insertion and extraction, conductive agents are also included to improve the conductivity of the electrode. Carbon materials are widely used as conductive agents included in electrodes. Summary of the Invention
[0004] According to an embodiment, an electrode is provided having a layer containing an active material comprising an oxide active material and fibrous carbon. The brightness exhibits periodic variations in a specific direction on the main surface of the active material layer.
[0005] According to other embodiments, a secondary battery is provided, which includes a positive electrode, a negative electrode, and an electrolyte. The negative electrode is the electrode involved in the above embodiments.
[0006] According to other embodiments, a battery pack is provided which includes the secondary battery involved in the above embodiments.
[0007] According to other embodiments, a vehicle is provided which includes the battery pack involved in the above embodiments.
[0008] Based on the electrodes constructed as described above, it is possible to provide electrodes for secondary batteries that can provide high yield and high rate performance in battery manufacturing, secondary batteries and battery packs with high rate performance, and vehicles equipped with the battery packs. Attached Figure Description
[0009] Figure 1 This is a cross-sectional view that schematically illustrates an example of the electrodes involved in the embodiment.
[0010] Figure 2 This is a partial cutaway perspective view schematically illustrating an example of a secondary battery involved in an embodiment.
[0011] Figure 3 It is Figure 2 The cross-sectional view is obtained by magnifying part A of the secondary battery shown.
[0012] Figure 4 This is a perspective view that schematically illustrates an example of a battery pack involved in an embodiment.
[0013] Figure 5 This is an exploded perspective view that schematically illustrates an example of a battery pack involved in an embodiment.
[0014] Figure 6 It means Figure 5 The diagram shows a block diagram of an example of the circuitry for the battery pack.
[0015] Figure 7 This is a partial perspective view that schematically represents an example of a vehicle involved in the implementation.
[0016] Figure 8 This is a diagram that schematically illustrates an example of a control system for the electrical system in a vehicle according to the embodiment.
[0017] Symbol Explanation 1…Electrode assembly, 2…Outer packaging component, 3…Negative electrode, 3a…Negative electrode current collector, 3b…Negative electrode layer containing active material, 3c…Negative electrode current collector tab, 4…Separator, 5…Positive electrode, 5a…Positive electrode current collector, 5b…Layer containing positive electrode active material, 6…Negative terminal, 7…Positive terminal, 10…Electrode, 10a…Current collector, 10b…Layer containing active material, 10c…Current collector tab, 11…Partial carbon heterogeneity, 12…Charge movement, 21… Busbar, 22… Positive side lead, 22a… Other end, 23… Negative side lead, 23a… Other end, 24… Adhesive tape, 31… Container, 32… Cover, 33… Protective sheet, 34… Printed circuit board, 35… Wiring, 40… Vehicle body, 41… Vehicle power supply, 42… Electrical control device, 43… External terminal, 44… Converter, 45… Drive motor, 100… Secondary battery, 200… Battery pack, 200a… Battery pack, 200b… battery pack, 200c… battery pack, 300… battery pack, 300a… battery pack, 300b… battery pack, 300c… battery pack, 301a… battery monitoring device, 301b… battery monitoring device, 301c… battery monitoring device, 342… positive side connector, 343… negative side connector, 345… thermistor, 346… protection circuit, 342a… wiring, 343a… wiring, 350 …External terminals for power supply, 352…positive terminal, 353…negative terminal, 348a…positive side wiring, 348b…negative side wiring, 400…vehicle, 411…battery management device, 412…communication bus, 413…positive terminal, 414…negative terminal, 415…switching device, 416…current detection unit, 417…negative input terminal, 418…positive input terminal, L1…connecting wire, L2…connecting wire, W…drive wheel.
[0018] To obtain electrodes with low resistance, large amounts of carbon materials such as granular carbon and fibrous carbon are typically added. However, excessive addition of carbon materials has resulted in a consistent tendency for carbon materials to aggregate within the electrode, particularly fibrous carbon, which is difficult to disperse. This aggregated carbon material clogs the gaps within the electrode, limiting the battery's rate performance. Conversely, when only a small amount of carbon material is added, the electrode's conductivity cannot be adequately ensured, leading to increased resistance.
[0019] Furthermore, electrostatic attraction between charged electrodes is a factor reducing manufacturing efficiency when using electrodes. For example, after the electrodes themselves are manufactured, they are sometimes moved to the manufacturing site where they are combined with other components to form a battery, and then the electrodes are transported one by one into the manufacturing apparatus. Electrostatic attraction can occur between the overlapping electrodes, resulting in poor transport.
[0020] The embodiments will now be described with reference to the accompanying drawings. It should be noted that common components in the embodiments are labeled with the same symbols, and repeated descriptions are omitted. Furthermore, the figures are schematic diagrams to facilitate the explanation and understanding of the embodiments; their shapes, dimensions, proportions, etc., may differ from actual devices, and appropriate design changes can be made with reference to the following description and well-known techniques. Detailed Implementation
[0021] (First Embodiment) According to a first embodiment, an electrode is provided. The electrode includes a layer containing an active material comprising an oxide active material and fibrous carbon. The brightness exhibits a periodic variation in a specific direction on the main surface of the active material layer.
[0022] The electrode is, for example, an electrode for a secondary battery. The secondary battery using the electrode can be a lithium secondary battery, or, for example, a non-aqueous electrolyte secondary battery containing a non-aqueous electrolyte. Furthermore, the term "electrode" here refers not only to an electrode cut to a size suitable for assembly into a battery, but also to an electrode ring (coil) before cutting. Alternatively, the electrode can be an electrode that has already been assembled into the battery and is removed from the disassembled battery.
[0023] In the electrode, although the fibrous carbon slightly aggregates on the main surface of the active material layer, i.e., the electrode surface, it is distributed in a uniform orientation. This ensures a conductive path along at least one direction along the main surface of the active material layer. Consequently, the electrode exhibits high rate capability and suppresses the rise in resistance within the electrode.
[0024] Furthermore, by having the fibrous carbon distributed unevenly in a periodic, patchy pattern, electrostatic adsorption, which is a cause of poor transfer when electrodes are overlapped, can be suppressed. Specifically, electrostatic adsorption can be prevented by discharging the charge accumulated on the surface of the layer containing the active material through the patchy carbon. It should be noted that the patchy distribution here is not limited to speckled patterns, but includes other periodic configurations such as island-like distributions or striped patterns.
[0025] In detail, on the main surface of the layer containing active material, carbon is locally and unevenly distributed along at least one direction with a period of 1 mm to 10 mm. Many oxide active materials, including titanium oxides, are white in their non-lithium-intercalated state. In contrast, carbon is black. Therefore, for the layer containing active material in the state where no lithium is intercalated in the oxide active material, the dispersion state of the oxide active material and carbon is highly correlated with the brightness of the surface of the layer containing active material. That is, the brightness is low in the parts of the layer containing active material where there is a lot of carbon on the oxide active material, and high in the parts where there is less carbon on the oxide active material. Thus, regarding the periodic change of brightness in at least one specific direction on the main surface of the layer containing active material, when the period of brightness variation is expressed as L(GV), the period of brightness variation can be expressed as 1 mm ≤ L(GV) ≤ 10 mm. Details are described below, but the period L (GV) of the brightness variation is determined by performing a Fourier transform on the brightness variation obtained from the moving average of the brightness variation in a specific direction, obtained by image analysis through the main surface of the layer containing the active material. Furthermore, the brightness amplitude is 0.3 cd / m² within the range of 1 mm ≤ L (GV) ≤ 10 mm. 2 Under the above circumstances, it can be determined that the brightness variation is periodic. It should be noted that one cycle of brightness variation here refers to the occurrence of one minimum and one maximum value in the brightness, that is, one cycle from the electrode surface turning black to white.
[0026] The electrode may further include a current collector. A layer containing active material may be formed on one or both sides of the current collector. The layer containing active material comprises an oxide active material and fibrous carbon as a conductive agent. The layer containing active material may further include optional other conductive agents and binders.
[0027] As an oxide active material, it is preferable to use materials capable of intercalating and deintercalating lithium ions (Li... + The layer containing the active material may also contain one type of oxide active material. Alternatively, the layer containing the active material may contain two or more types of oxide active materials. The oxide active material preferably contains titanium oxide.
[0028] Examples of titanium oxides include lithium titanate (e.g., Li) with an orthorhombic manganese oxide structure.2+y Ti3O7, 0≤y≤3), lithium titanate with spinel structure (e.g., Li), 4+x Ti5O 12 Examples of active oxides include: titanium dioxide (TiO2), anatase titanium dioxide, rutile titanium dioxide, alkali manganese oxide titanium composite oxide, orthorhombic titanium composite oxide, and monoclinic niobium titanium oxide. Other examples of active oxides include niobium pentoxide (Nb2O5).
[0029] As examples of the aforementioned histogram-type titanium-containing composite oxides, Li can be cited. 2+a M I 2-b Ti 6-c M II d O 14+σ The compound represented. Wherein, M I It is selected from at least one of the groups consisting of Sr, Ba, Ca, Mg, Na, Cs, Rb, and K. M II The composition is selected from at least one element in the group consisting of Zr, Sn, V, Nb, Ta, Mo, W, Y, Fe, Co, Cr, Mn, Ni, and Al. The subscripts in the composition formula are 0 ≤ a ≤ 6, 0 ≤ b < 2, 0 ≤ c < 6, 0 ≤ d < 6, and -0.5 ≤ σ ≤ 0.5. As a specific example of a histogram-type titanium-containing composite oxide, Li can be cited. 2+a Na2Ti6O 14 (0≤a≤6).
[0030] As examples of the aforementioned monoclinic niobium titanium oxides, Li can be cited. x Ti 1-y M1 y Nb 2-z M2 z O 7+δ The compounds referred to herein. M1 is at least one compound selected from the group consisting of Zr, Si, and Sn. M2 is at least one compound selected from the group consisting of V, Ta, and Bi. The subscripts in the composition formulas are 0 ≤ x ≤ 5, 0 ≤ y < 1, 0 ≤ z < 2, and -0.3 ≤ δ ≤ 0.3. As a specific example of monoclinic niobium titanium oxides, Li can be cited. x Nb2TiO7 (0≤x≤5).
[0031] Other examples of monoclinic niobium titanium oxides include Li x Ti 1-y M3 y+z Nb 2-z O 7-δThe compound represented is M3, which is selected from at least one of Mg, Fe, Ni, Co, W, Ta, and Mo. The subscripts in the constituent formulas are 0≤x≤5, 0≤y<1, 0≤z<2, and -0.3≤δ≤0.3.
[0032] Conductive agents are formulated to improve current-collecting performance and suppress contact resistance between the active material and the current collector. As a conductive agent, it contains at least fibrous carbon. The fibrous material moderately aggregates within the layer containing the active material, existing in a non-uniform, periodic patchy distribution. Conversely, if there is little aggregation and the carbon distribution is highly uniform, it will not form a patchy distribution. On the other hand, excessive aggregation will impair the periodicity of the carbon distribution.
[0033] Examples of fibrous carbon include carbon nanotubes and carbon nanofibers such as vapor-grown carbon fiber (VGCF), single-layer carbon nanotubes (SWCNT), or multilayer carbon nanotubes (FWCNT). One of them may be included as fibrous carbon, or two or more may be combined to include fibrous carbon.
[0034] Fibrous carbon can take a specific orientation within a layer containing active material. Details are described below, but for example, a slurry containing oxide active material and a conductive agent can be used to form the layer containing active material. When the slurry is subjected to high shear, carbon with a high aspect ratio tends to oriented along the shear direction. Therefore, by using fibrous carbon as a conductive agent, it is easy to form a layer containing active material where carbon exists in a patchy, non-uniform manner. The higher the aspect ratio, the easier it is to orient when sheared in the slurry; therefore, carbon with a higher aspect ratio is preferred. Specifically, the fibrous carbon preferably has a fiber length of 10 μm or more and 100 μm or less. Furthermore, the fiber diameter of the fibrous carbon is preferably 50 nm or less.
[0035] In addition to the aforementioned fibrous carbon, other conductive agents can be further included in the layer containing the active material. Examples of other conductive agents include carbon black such as acetylene black and graphite. One of them can be used as another conductive agent, or two or more can be combined as another conductive agent. It should be noted that when flake-shaped graphite is included, the graphite flakes can have a periodic distribution that is longer than that obtained with fibrous carbon. However, with respect to graphite flakes, since the intensity of brightness tends to vary randomly, the amplitude of the brightness spectrum after the Fourier transform, which represents the intensity of the periodicity, becomes weaker. Therefore, the non-uniform distribution of fibrous carbon mainly reflects the period L (GV) of brightness variation.
[0036] The proportion of the conductive agent in the layer containing the active material is preferably 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the oxide active material. On the other hand, by setting the amount of conductive agent relative to 100 parts by mass of the oxide active material to 0.1 parts by mass or more, the current-collecting performance of the layer containing the active material can be improved. Furthermore, controlling the amount of conductive agent relative to 100 parts by mass of the oxide active material to 20 parts by mass or less is preferred from the perspective of achieving high capacity. Moreover, if it is 20 parts by mass or less, the amount of conductive agent relative to 100 parts by mass of the oxide active material will not become excessive, and the periodicity of the carbon distribution in the layer containing the active material can be maintained. The conductive agent preferably contains 0.1 parts by mass or more and 5 parts by mass or less of fibrous carbon relative to 100 parts by mass of the oxide active material.
[0037] The binder is formulated to fill the gaps between the dispersed oxide active material and to bond the oxide active material to the current collector. Examples of binders include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluororubber, styrene-butadiene rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC), and salts of CMC. One of these can be used as a binder, or a combination of two or more can be used as a binder. It should be noted that styrene-butadiene rubber, CMC, and salts of CMC can also function as thickeners. The proportion of binder in the layer containing the active material is preferably 2 parts by mass or more and 44 parts by mass or less relative to 100 parts by mass of the oxide active material. On the other hand, by setting the amount of binder relative to 100 parts by mass of the oxide active material to 2 parts by mass or more, the adhesion between the layer containing the active material and the current collector becomes sufficient, and excellent cycling performance can be expected. On the other hand, it is preferable to control the amount of binder relative to 100 parts by mass of oxide active material to 44 parts by mass or less in order to achieve high capacity.
[0038] The current collector uses an electrochemically stable material at the potential for lithium (Li) insertion and extraction from the oxide active material. For example, when using an oxide active material as the negative electrode active material, the current collector is preferably made of copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing one or more elements selected from Mg, Ti, Zn, Mn, Fe, Cu, and Si. The thickness of the current collector is preferably 5 μm or more and 20 μm or less. A current collector with such a thickness achieves a balance between electrode strength and lightweight.
[0039] Furthermore, the current collector can be contained in the portion of its surface where no layer containing active material is formed. This portion can function as a current collector tab.
[0040] Next, the electrodes involved in the embodiments will be described in more detail with reference to the accompanying drawings.
[0041] Figure 1 This is a cross-sectional view that roughly represents an example of an electrode. Figure 1 The electrode 10 shown includes a current collector 10a and layers 10b containing active material supported on both sides of the current collector 10a. One side of the current collector 10a includes a portion on which neither surface supports the layer 10b containing active material. This portion functions as a current collector tab 10c.
[0042] exist Figure 1 In the diagram, the carbon non-uniformity portion 11, where fibrous carbon is periodically and unevenly distributed on the main surface of the active material layer 10b located on both sides of the electrode 10, is represented by dashed lines. Furthermore, arrows indicate charge movement 12 on each main surface. As shown in the diagram, the surface charge accumulated on the main surface of the active material layer 10b is discharged via the carbon non-uniformity portion 11. This prevents electrostatic adsorption between the electrodes 10, thus improving the yield of battery manufacturing. It should be noted that... Figure 1 The arrow representing the movement of charge 12 is exaggerated in order to make it easy to visually confirm, but the trajectory of the charge is not limited to the case shown by the arrow.
[0043] <Manufacturing Method> Electrodes can be fabricated, for example, by the following method. First, a slurry is prepared by suspending an oxide active material, a conductive agent, and a binder in a solvent. Optionally, a thickener and a dispersant may be further added to the slurry. Additionally, the binder may function as a thickener. This slurry is then coated onto one or both sides of a current collector. Next, the coated slurry is dried to obtain a laminate containing the active material and the current collector. This laminate is then pressed. Electrodes are fabricated by operating in this manner.
[0044] Here, by appropriately controlling the conditions of the prepared slurry and the coating conditions of the slurry on the current collector, the carbon distribution can exhibit periodicity.
[0045] When the powder material, i.e., the oxide active material, the carbon conductive agent, and the binder are well wetted and dispersed in the slurry, the periodicity of the carbon distribution decreases. Specifically, if the powder material particles do not aggregate, or if a dispersant is used and the dispersant adsorbs onto the particle surface and stabilizes the particles, carbon is less likely to exist in a localized state. Conversely, even if there is excessive aggregation of the oxide powder as the active material or the carbon as the conductive agent, periodicity in the carbon distribution is not easily observed. This state arises from poor dispersion of the powder material in the slurry, sometimes due to insufficient dispersion time or dispersion intensity.
[0046] The orientation of the carbon conductive agent within the slurry during coating of the current collector also affects the periodicity of carbon distribution in the resulting layer containing active material. If fibrous carbon is subjected to high shear in the slurry, the stabilized agglomerate structure is destroyed, making it more prone to orientation along the shear direction. This agglomerate structure breakdown sometimes exhibits periodic variations as the internal structure is broken down in stages. Even when the same shear is applied, structural damage may or may not occur. The presence or absence of such structural damage indicates periodic behavior. For example, the breakdown of the agglomerate structure is more likely to occur in areas near the die wall where strong shear is applied, leading to the orientation of fibrous carbon in the electrode coating surface. This can cause periodic variations in the amount of carbon on the electrode surface, and even periodic variations in brightness.
[0047] By using a slurry composition and coating conditions that cause the aforementioned aggregation and orientation of fibrous carbon, a periodic variation in the carbon content on the electrode surface can be achieved. Specifically, using fibrous carbon with longer fiber lengths results in a wider amplitude of carbon content fluctuations, making it easier to exhibit a periodic tendency. Furthermore, moderately increasing the amount of fibrous carbon added tends to exhibit a periodicity; for example, it is preferable to add 0.1 to 5 parts by mass of fibrous carbon per 100 parts by mass of oxide active material. Using a low molecular weight thickener to adjust the solids content of the slurry to a higher level also makes it easier to exhibit a periodicity. For example, preparing a slurry with a non-volatile content (NV) of 60% or more. Furthermore, the use of dispersants that promote the aggregation of conductive agents or active materials tends to exhibit a periodicity. Additionally, reducing the thickness of the shim used in the die for coating the slurry increases the shear stress on the slurry. Furthermore, increasing the transport speed of the current collector in the coating slurry reduces the thickness of the slurry film, but in this case, the shear stress on the slurry also increases. As a result, the orientation of the fibrous carbon becomes stronger, as described above, and it becomes easier to exhibit periodicity. Furthermore, if the slurry is allowed to stand for a long time after the powder material in it is dispersed, the fibrous carbon can slightly re-aggregate. If shearing is applied to the moderately re-aggregated fibrous carbon, the orientation of the fibrous carbon in the resulting electrode can be increased.
[0048] <Determination Method> Next, the method for measuring the change in brightness on the main surface of the layer containing active substances, and the method for measuring the active substances will be explained.
[0049] It should be noted that the electrode being measured can be, for example, an electrode that has been cut to a size suitable for assembly into the battery, or an electrode ring (coil) before cutting. Alternatively, the electrode that has already been assembled into the battery can be removed from the battery for measurement.
[0050] Measurement of brightness The variation in brightness on the main surface of the layer containing active substances can be measured as follows.
[0051] First, the battery is set to a state where lithium ions are completely removed from the active material contained in the electrode. For example, if the electrode is used as the negative electrode of the battery, the battery is set to a fully discharged state. For example, by repeatedly discharging the battery at 0.1C in an environment of 25°C until the rated termination voltage or the battery voltage reaches 1.0V, the battery can be set to a discharged state by making the discharge current value less than 1 / 100 of the rated capacity. Next, the battery is disassembled in an argon-filled glove box, the electrode is removed, and washed with a suitable solvent. For example, ethyl methyl carbonate can be used as a suitable solvent. The washed electrode is dried and used as a test sample.
[0052] For the prepared electrode samples, brightness linearity analysis was performed using image analysis software. ImageJ, as shown in the non-patent literature (Dr. Michael et al., Image Processing with ImageJ, Biophotonics International, July 2004), can be used as an example.
[0053] First, for image data obtained from photographing the main surface of the layer containing the active material, the brightness of any line is acquired. For the image data, it is preferable to use image data with minimal influence from uneven brightness from the light source and a size of 5 cm on each side. If the size is too small, the average information is insufficient; if it is too large, there are insufficient pixels relative to the period width of the object. A moving average of 20 adjacent values is calculated relative to the brightness variation along the acquired line, and this average is used as the background. The reason for using the moving average is to remove noise caused by the light source during the original image data acquisition. The difference between the brightness value at each measurement point and the background is calculated. A high-speed Fourier transform is performed on the brightness data along the line after removing the background to obtain the normalized amplitude at each frequency.
[0054] For the axial direction of linear analysis, it is preferably taken in the direction intersecting with or along the coating direction of the slurry during electrode fabrication on the main surface of the layer containing the active material. It is preferable to take the axial direction of linear analysis in a direction that becomes perpendicular or parallel to the slurry coating direction. This is because: when the periodic change in the brightness of the electrode surface is perpendicular to the coating direction, it teaches the effect of the collapse of the slurry's agglomerated structure; when it is parallel, it teaches the effect of the orientation of the fibrous conductive agent. For example, for a rectangular electrode, the line is set in a direction along any one of the four sides.
[0055] Determination of active substances The crystal structure of the active substance can be confirmed, for example, by combining powder X-ray diffraction (XRD) with analytical methods using the Rietveld method. The composition of the active substance can be analyzed, for example, using inductively coupled plasma (ICP) luminescence spectrophotometry.
[0056] Powder X-ray diffraction determination of active substances can be performed, for example, as follows.
[0057] First, the system is set to a state where lithium ions are completely removed from the active material (e.g., titanium oxide) contained in the electrode. For example, when the electrode is used as the negative electrode of a battery, the battery is set to a fully discharged state under the conditions described above. This allows observation of the crystallization state of the active material. Even in the discharged state, residual lithium ions may sometimes remain. Due to the influence of lithium ions remaining in the electrode, impurity phases such as lithium carbonate or lithium fluoride may sometimes be mixed into the powder X-ray diffraction results. The introduction of impurity phases can be prevented, for example, by setting the measurement atmosphere to an inert gas atmosphere or by washing the electrode surface. Even if impurity phases are present, they can be ignored and resolved in the case of XRD.
[0058] Next, the battery is disassembled and the electrodes are removed in an argon-filled glove box. The removed electrodes are then washed with a suitable solvent, such as ethyl methyl carbonate. The washed electrodes are then cut to an area approximately the same as the area of the holder of the powder X-ray diffractometer, and used as the test sample.
[0059] The cut sample (electrode) is directly attached to a glass holder for measurement. At this time, the position of the peak originating from the current collector is pre-determined. In addition, the peaks of other components such as the conductive agent and binder are also pre-determined. In cases where the peak of the current collector overlaps with the peak of the active material, it is preferable to peel off the layer containing the active material from the current collector for measurement. This is to separate the overlapping peaks when quantitatively measuring the peak intensity. For example, the layer containing the active material can be peeled off by irradiating the electrode with ultrasound in a solvent. The layer containing the active material is sealed in a capillary tube and placed on a rotating sample stage for measurement. This method allows for obtaining an XRD pattern of the active material while minimizing the influence of orientation. The obtained XRD pattern must be applicable to Rietveld analysis. To collect Rietveld data, the measurement time and / or X-ray intensity are appropriately adjusted so that the step size is 1 / 3 to 1 / 5 of the minimum half-width of the diffraction peak, and the intensity at the position of the most intense reflection peak is counted in increments of 10,000.
[0060] The obtained XRD pattern was analyzed using the Rietveld method. In the Rietveld method, the diffraction pattern is calculated from a pre-estimated crystal structure model. By fully fitting the calculated values to the measured values, parameters related to the crystal structure (lattice constant, atomic coordinates, occupancy, etc.) can be precisely analyzed. This allows for the investigation of the characteristics of the crystal structure of the synthesized oxide. Furthermore, it allows for the investigation of the occupancy of each point of the constituent elements.
[0061] Methods for confirming the composition of active substances The composition of the active substance can be analyzed, for example, using inductively coupled plasma (ICP) luminescence spectrophotometry. In this case, the molar ratio of each element depends on the sensitivity of the analytical apparatus used. Therefore, the measured molar ratio may sometimes deviate from the actual molar ratio by a value corresponding to the error value of the measuring apparatus. However, even if the value deviates from the actual molar ratio within the error range of the analytical apparatus, the performance of the active substance involved in the embodiment can still be fully realized.
[0062] The determination of the composition of active substances contained in an electrode by ICP emission spectrometry is carried out through the following steps.
[0063] When the electrode being measured is assembled into the battery, the electrode is removed from the battery and washed using the steps described in the section on powder X-ray diffraction.
[0064] The layer containing the active material is peeled off from the electrode. For example, the layer containing the active material can be peeled off by irradiating it with ultrasound. As a specific example, the layer containing the active material can be peeled off from the current collector by placing the electrode in ethyl methyl carbonate added to a glass beaker and vibrating it in an ultrasonic cleaner.
[0065] Next, the detached portion is briefly heated in the atmosphere (e.g., at approximately 500°C for about 1 hour) to burn off unwanted components such as the binder and conductive agent. By dissolving this residue with acid, a liquid sample containing the active substance can be prepared. Hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, etc., can be used as the acid. By performing ICP analysis on this liquid sample, the composition of the active substance can be determined.
[0066] The electrode according to the first embodiment has a layer containing an active material including an oxide active material and fibrous carbon, and the brightness of the active material layer exhibits periodic changes in a specific direction on its main surface. Therefore, the electrode can improve the yield of battery manufacturing and provide a rechargeable battery with high rate performance.
[0067] (Second Implementation) According to a second embodiment, a secondary battery is provided, comprising a negative electrode, a positive electrode, and an electrolyte. This secondary battery includes the electrode described in the first embodiment as the negative electrode.
[0068] The secondary battery may further include a separator disposed between the positive and negative electrodes. The negative electrode, positive electrode, and separator can constitute an electrode assembly. The electrolyte can be retained in the electrode assembly.
[0069] Furthermore, the secondary battery may further include an outer packaging component that houses the electrode assembly and electrolyte.
[0070] Furthermore, the secondary battery may further include a negative terminal electrically connected to the negative electrode and a positive terminal electrically connected to the positive electrode.
[0071] The secondary battery may be, for example, a lithium secondary battery. Furthermore, the secondary battery includes a non-aqueous electrolyte secondary battery containing a non-aqueous electrolyte.
[0072] The following provides a detailed description of the negative electrode, positive electrode, electrolyte, diaphragm, outer packaging components, negative terminal, and positive terminal.
[0073] 1) Negative electrode The negative electrode may include a negative current collector and a negative electrode layer containing active material. The negative current collector and the negative electrode layer containing active material may be the current collector and the active material layer included in the electrode according to the first embodiment, respectively.
[0074] Parts of the detailed description of the negative electrode that overlap with the details described for the first embodiment are omitted.
[0075] The density of the active material-containing layer of the negative electrode (excluding the current collector) is preferably 1.8 g / cm 3 or more and 2.8 g / cm 3 or less. A negative electrode in which the density of the active material-containing layer of the negative electrode falls within this range is excellent in energy density and electrolyte retention. The density of the active material-containing layer of the negative electrode is more preferably 2.1 g / cm 3 or more and 2.6 g / cm 3 or less.
[0076] 2) Positive Electrode The positive electrode may include a positive electrode current collector and a positive electrode active material-containing layer. The positive electrode active material-containing layer may be formed on one side or both sides of the positive electrode current collector. The positive electrode active material-containing layer may include a positive electrode active material and an optional conductive agent and binder.
[0077] As the positive electrode active material, for example, an oxide or a sulfide can be used. The positive electrode may include one type of compound alone as the positive electrode active material, or may include two or more types of compounds in combination. Examples of the oxides and sulfides include compounds capable of intercalating and deintercalating Li or Li ions.
[0078] Such compounds include, for example, manganese dioxide (MnO₂), iron oxide, copper oxide, nickel oxide, lithium manganese composite oxide (for example, Li x Mn₂O₄ or Li x MnO₂; 0<x≤1), lithium nickel composite oxide (for example, Li x NiO₂; 0<x≤1), lithium cobalt composite oxide (for example, Li x CoO₂; 0<x≤1), lithium nickel cobalt composite oxide (for example, Li x Ni 1-y Co y O₂; 0<x≤1, 0<y<1), lithium manganese cobalt composite oxide (for example, Li x Mn y Co 1-y O₂; 0<x≤1, 0<y<1), lithium manganese nickel composite oxide having a spinel structure (for example, Li x Mn 2-y Ni y O₄; 0<x≤1, 0<y<2), lithium phosphorus oxide having an olivine structure (for example, Li x FePO₄; 0<x≤1, Li x Fe 1-y Mn y PO₄; 0<x≤1, 0<y≤1, Lix CoPO₄; 0<x≤1), iron sulfate (Fe₂(SO₄)₃), vanadium oxide (e.g., V₂O₅) and lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O₂; 0<x≤1, 0<y<1, 0<z<1, y+z<1).
[0079] In the above, examples of more preferable compounds as the positive electrode active material include lithium manganese composite oxides having a spinel structure (e.g., Li x Mn₂O₄; 0<x≤1), lithium nickel composite oxides (e.g., Li x NiO₂; 0<x≤1), lithium cobalt composite oxides (e.g., Li x CoO₂; 0<x≤1), lithium nickel cobalt composite oxides (e.g., Li x Ni 1-y Co y O₂; 0<x≤1, 0<y<1), lithium manganese nickel composite oxides having a spinel structure (e.g., Li x Mn 2-y Ni y O₄; 0<x≤1, 0<y<2), lithium manganese cobalt composite oxides (e.g., Li x Mn y Co 1-y O₂; 0<x≤1, 0<y<1), lithium iron phosphate (e.g., Li x FePO₄; 0<x≤1) and lithium nickel cobalt manganese composite oxides (Li x Ni 1-y-z Co y Mn z O₂; 0<x≤1, 0<y<1, 0<z<1, y+z<1). When these compounds are used for the positive electrode active material, the positive electrode potential can be increased.
[0080] In the case of using a room-temperature molten salt as the electrolyte of the battery, it is preferable to use a positive electrode active material containing lithium iron phosphate, Li x VPO₄F (0≤x≤1), lithium manganese composite oxide, lithium nickel composite oxide, lithium nickel cobalt composite oxide, or a mixture thereof. These compounds have low reactivity with the room-temperature molten salt, and thus can improve the cycle life. Details of the room-temperature molten salt will be described later.
[0081] The primary particle diameter of the positive electrode active material is preferably 100 nm or more and 1 μm or less. The positive electrode active material having a primary particle diameter of 100 nm or more is easy to handle in industrial production. The positive electrode active material having a primary particle diameter of 1 μm or less can allow the solid-state diffusion of lithium ions to proceed smoothly.
[0082] The specific surface area of the positive electrode active material is preferably 0.1 m². 2 / g or more and 10m 2 / g or less. Has 0.1m 2 Positive electrode active materials with a specific surface area of over / g can adequately ensure the insertion and extraction sites of Li ions. With a specific surface area of 10m... 2 Positive electrode active materials with a specific surface area of less than / g are easy to handle in industrial production and can ensure good charge-discharge cycle performance.
[0083] The binder is used to fill the gaps between the dispersed positive electrode active material and to bond the positive electrode active material to the positive electrode current collector. Examples of binders include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluororubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC), and salts of CMC. One of these can be used as a binder, or a combination of two or more can be used as a binder.
[0084] Conductive agents are used to improve current collection performance and suppress the contact resistance between the positive electrode active material and the positive electrode current collector. Examples of conductive agents include vapor-grown carbon fiber (VGCF), carbon black such as acetylene black, and carbonaceous materials such as graphite. One of them can be used as a conductive agent, or two or more can be combined as a conductive agent. Alternatively, the conductive agent can be omitted.
[0085] In the layer containing the positive electrode active material, the positive electrode active material and the binder are preferably mixed in proportions of 80% or more and 98% or less by mass, and 2% or more and 20% or less by mass, respectively.
[0086] Sufficient electrode strength can be obtained by setting the amount of binder to 2% by mass or more. Furthermore, the binder functions as an insulator. Therefore, if the amount of binder is set to 20% by mass or less, the amount of insulator contained in the electrode is reduced, thereby reducing internal resistance.
[0087] When a conductive agent is added, the positive electrode active material, binder and conductive agent are preferably mixed in proportions of 77% or more and 95% or less by mass, 2% or more and 20% or less by mass, and 3% or more and 15% or less by mass, respectively.
[0088] The aforementioned effects can be achieved by setting the amount of the conductive agent to 3% by mass or more. Furthermore, by setting the amount of the conductive agent to 15% by mass or less, the proportion of the conductive agent in contact with the electrolyte can be reduced. At this low proportion, electrolyte decomposition can be reduced under high-temperature storage conditions.
[0089] The positive current collector is preferably aluminum foil or aluminum alloy foil containing one or more elements selected from Mg, Ti, Zn, Ni, Cr, Mn, Fe, Cu and Si.
[0090] The thickness of the aluminum foil or aluminum alloy foil is preferably 5 μm or more and 20 μm or less, more preferably 15 μm or less. The purity of the aluminum foil is preferably 99% by mass or more. The content of transition metals such as iron, copper, nickel, and chromium contained in the aluminum foil or aluminum alloy foil is preferably 1% by mass or less.
[0091] Furthermore, the positive current collector can be included in the portion of its surface where no layer containing the positive active material is formed. This portion can function as a positive current collector tab.
[0092] The positive electrode can be manufactured, for example, by the following method. First, a slurry is prepared by suspending the positive electrode active material, a conductive agent, and a binder in a solvent. This slurry is then coated onto one or both sides of the current collector. Next, the coated slurry is dried to obtain a laminate containing the positive electrode active material and the current collector. Afterward, the laminate is pressed. The positive electrode is manufactured by operating in this manner.
[0093] Alternatively, the positive electrode can be manufactured using the following method. First, the positive electrode active material, conductive agent, and binder are mixed to obtain a mixture. Next, this mixture is shaped into granules. Then, by placing these granules onto a current collector, the positive electrode can be obtained.
[0094] 3) Electrolytes As the electrolyte, for example, a liquid non-aqueous electrolyte or a gel-like non-aqueous electrolyte can be used. A liquid non-aqueous electrolyte is prepared by dissolving an electrolyte salt, which is the solute, in an organic solvent. The concentration of the electrolyte salt is preferably 0.5 mol / L or higher and 2.5 mol / L or lower.
[0095] Examples of electrolyte salts include lithium salts such as lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), and lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2), as well as mixtures thereof. The electrolyte salt is preferably a substance that is difficult to oxidize even at high potentials, and LiPF6 is most preferred.
[0096] Examples of organic solvents include cyclic carbonates such as propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC); chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl ethyl carbonate (MEC); cyclic ethers such as tetrahydrofuran (THF), 2-methyl tetrahydrofuran (2MeTHF), and dioxolane (DOX); chain ethers such as dimethoxyethane (DME) and diethoxyethane (DEE); γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane (SL). These organic solvents can be used alone or as mixed solvents.
[0097] Gel-like nonaqueous electrolytes are prepared by compounding liquid nonaqueous electrolytes with polymeric materials. Examples of polymeric materials include polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyethylene oxide (PEO), or mixtures thereof.
[0098] Alternatively, as a non-aqueous electrolyte, in addition to liquid non-aqueous electrolytes and gel non-aqueous electrolytes, room-temperature molten salts (ionic melts) containing lithium ions, polymeric solid electrolytes, and inorganic solid electrolytes can also be used.
[0099] Room-temperature molten salts (ionic melts) refer to compounds that exist as liquids at room temperature (above 15°C and below 25°C) in organic salts formed by the combination of organic cations and anions. Room-temperature molten salts include those existing as liquids in monomeric form, those that become liquids by mixing with electrolyte salts, those that become liquids by dissolving in organic solvents, or mixtures thereof. Generally, the melting point of room-temperature molten salts used in secondary batteries is below 25°C. Furthermore, the organic cations typically possess a quaternary ammonium framework.
[0100] Polymer solid electrolytes can be prepared by dissolving electrolyte salts in polymer materials and then solidifying them.
[0101] The inorganic solid electrolyte is a solid substance having Li ion conductivity. The expression "having Li ion conductivity" as used herein means exhibiting 1×10 -6 S / cm or higher lithium ion conductivity at 25°C. Examples of the inorganic solid electrolyte include an oxide-based solid electrolyte or a sulfide-based solid electrolyte. Specific examples of the inorganic solid electrolyte are as follows.
[0102] As the oxide-based solid electrolyte, it is preferable to use a lithium phosphate solid electrolyte having a NASICON (Sodium (Na) Super Ionic Conductor) type structure and represented by the general formula Li 1+x Mα₂(PO₄)₃. Mα in the above general formula is, for example, one or more selected from the group consisting of titanium (Ti), germanium (Ge), strontium (Sr), zirconium (Zr), tin (Sn), aluminum (Al) and calcium (Ca). The subscript x is in the range of 0≤x≤2.
[0103] As specific examples of the lithium phosphate solid electrolyte having a NASICON type structure, mention may be made of LATP compounds represented by Li 1+ x Al x Ti 2-x (PO₄)₃ with 0.1≤x≤0.5; compounds represented by Li 1+x Al y Mβ 2-y (PO₄)₃, where Mβ is one or more selected from the group consisting of Ti, Ge, Sr, Zr, Sn and Ca, and 0≤x≤1 and 0≤y≤1; compounds represented by Li 1+x Al x Ge 2-x (PO₄)₃ with 0≤x≤2; and compounds represented by Li 1+x Al x Zr 2-x (PO₄)₃ with 0≤x≤2; compounds represented by Li 1+x+ y Al x Mγ 2-x Si y P 3-y O 12 , where Mγ is one or more selected from the group consisting of Ti and Ge, 0<x≤2 and 0≤y<3; and compounds represented by Li 1+2x Zr 1-x Ca x (PO₄)₃ with 0≤x<1.
[0104] In addition to the aforementioned lithium phosphate solid electrolyte, other oxide-based solid electrolytes, such as those based on Li... x PO y N z This refers to amorphous LIPON compounds (e.g., Li) where 2.6 ≤ x ≤ 3.5, 1.9 ≤ y ≤ 3.8, and 0.1 ≤ z ≤ 1.3. 2.9 PO 3.3 N 0.46 ); Garnet-type structure with La 5+x A x La 3-x Mδ2O 12 This indicates a compound in which A is selected from one or more of the group consisting of Ca, Sr, and Ba, and Mδ is selected from one or more of the group consisting of Nb and Ta, with 0 ≤ x ≤ 0.5; and Li3Mδ 2-x L2O 12 This indicates that Mδ is a compound selected from one or more species in the group consisting of Nb and Ta, and L may contain Zr and 0 ≤ x ≤ 0.5; with Li 7-3x Al x La3Zr3O 12 Represents compounds in which 0 ≤ x ≤ 0.5; in Li 5+x La3Mδ 2-x Zr x O 12 Mδ represents an LLZ compound selected from the group consisting of Nb and Ta, where 0 ≤ x ≤ 2 (e.g., Li7La3Zr2O). 12 ); and those with a perovskite-type structure and La 2 / 3-x Li x TiO3 represents compounds in which 0.3 ≤ x ≤ 0.7.
[0105] One or more of the above-mentioned compounds may be used as a solid electrolyte. Two or more of the above-mentioned solid electrolytes may also be used.
[0106] 4) Diaphragm The diaphragm can be formed, for example, from a porous membrane containing polyethylene (PE), polypropylene (PP), cellulose, or polyvinylidene fluoride (PVdF), or a nonwoven fabric made of synthetic resin. From a safety point of view, porous membranes made of polyethylene or polypropylene are preferred because these porous membranes melt at a certain temperature and can interrupt the current.
[0107] 5) Outer packaging components As outer packaging components, containers made of laminated film or metal containers can be used, for example.
[0108] The thickness of the laminate is, for example, 0.5 mm or less, preferably 0.2 mm or less.
[0109] As a laminated film, a multilayer film comprising multiple resin layers and a metal layer sandwiched between these resin layers is used. The resin layers include, for example, polymeric materials such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET). For weight reduction, the metal layer is preferably made of aluminum foil or aluminum alloy foil. The laminated film is sealed using hot-melt bonding and can be shaped into an outer packaging component.
[0110] The thickness of the wall of the metal container is, for example, 1 mm or less, more preferably 0.5 mm or less, and even more preferably 0.2 mm or less.
[0111] Metal containers are made of materials such as aluminum or aluminum alloys. The aluminum alloy preferably contains elements such as magnesium, zinc, and silicon. When the aluminum alloy contains transition metals such as iron, copper, nickel, and chromium, their content is preferably less than 100 ppm by mass.
[0112] There are no particular limitations on the shape of the outer packaging components. The outer packaging components can be, for example, flat (thin), square, cylindrical, coin-shaped, or button-shaped. The outer packaging components can be appropriately selected based on the battery size or intended use.
[0113] 6) Negative extremes The negative terminal can be formed from a material that is electrochemically stable and conductive at the Li insertion / deintercalation potential of the aforementioned negative electrode active material. Specifically, examples of materials for the negative terminal include copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. Aluminum or an aluminum alloy is preferred as the material for the negative terminal. To reduce the contact resistance with the negative electrode current collector, the negative terminal is preferably made of the same material as the negative electrode current collector.
[0114] 7) Positive extreme The positive terminal can be located in a potential range of 3V or higher and 4.5V or lower relative to the redox potential of lithium (vs. Li / Li). + The positive terminal is formed of a material that is electrically stable and conductive. Examples of materials for the positive terminal include aluminum, or aluminum alloys containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. To reduce the contact resistance with the positive current collector, the positive terminal is preferably formed of the same material as the positive current collector.
[0115] Next, the secondary battery involved in the implementation method will be described in more detail with reference to the accompanying drawings.
[0116] Figure 2 This is a partial cutaway perspective view schematically representing an example of a secondary battery. Figure 3 It is Figure 2 The cross-sectional view is obtained by magnifying part A of the secondary battery shown.
[0117] Figure 2 and Figure 3 The secondary battery 100 shown has Figure 2 and Figure 3 Electrode group 1 shown Figure 2 The outer packaging component 2 and the electrolyte (not shown) are shown. The electrode assembly 1 and the electrolyte are housed within the outer packaging component 2. The electrolyte is held within the electrode assembly 1.
[0118] The outer packaging component 2 is made of a laminated film containing two resin layers and a metal layer sandwiched between them.
[0119] Electrode group 1 as follows Figure 3 The electrode assembly shown is a stacked type. The stacked type electrode assembly 1 has a structure in which a negative electrode 3 and a positive electrode 5 are sandwiched between a diaphragm 4 and stacked alternately.
[0120] The electrode assembly 1 includes multiple negative electrodes 3. Each negative electrode 3 has a negative current collector 3a and a layer 3b containing active material on both sides of the negative current collector 3a. Furthermore, the electrode assembly 1 includes multiple positive electrodes 5. Each positive electrode 5 has a positive current collector 5a and a layer 5b containing active material on both sides of the positive current collector 5a.
[0121] Each negative electrode 3's negative electrode current collector 3a includes a portion on one side of which does not have a layer 3b supporting the negative electrode active material on any surface. This portion functions as the negative electrode current collector tab 3c. Figure 3 As shown, the negative collector tab 3c does not overlap with the positive electrode 5. Furthermore, multiple negative collector tabs 3c are electrically connected to a strip-shaped negative terminal 6. The front end of the strip-shaped negative terminal 6 is led out to the outside of the outer packaging component 2.
[0122] Furthermore, although not shown, each positive electrode 5's positive current collector 5a includes a portion on one side of which does not support a layer 5b containing the positive active material on any surface. This portion functions as a positive current collector tab. The positive current collector tab, like the negative current collector tab 3c, does not overlap with the negative electrode 3. Moreover, the positive current collector tab is located on the opposite side of the electrode group 1 relative to the negative current collector tab 3c. The positive current collector tab is electrically connected to the strip-shaped positive terminal 7. The front end of the strip-shaped positive terminal 7 is located on the opposite side of the negative terminal 6 and is led out to the outside of the outer packaging member 2.
[0123] The secondary battery according to the second embodiment includes the electrodes according to the first embodiment. Therefore, the secondary battery can be manufactured with a high yield and can exhibit high rate performance.
[0124] (Third implementation) According to a third embodiment, a battery pack is provided. The battery pack includes a plurality of secondary batteries as described in the second embodiment.
[0125] In the battery pack, the individual cells can be electrically connected in series or in parallel, or a combination of series and parallel connections can be configured.
[0126] Next, an example of a battery pack involved in the embodiment will be described with reference to the accompanying drawings.
[0127] Figure 4 This is a three-dimensional diagram that roughly represents an example of a battery pack. Figure 4 The battery pack 200 shown includes five individual cells 100a to 100e, four busbars 21, a positive electrode lead 22, and a negative electrode lead 23. Each of the five individual cells 100a to 100e is a secondary battery according to the second embodiment.
[0128] Bus 21 connects, for example, the negative terminal 6 of a single cell 100a to the positive terminal 7 of the adjacent single cell 100b. In this manner, five single cells 100 are connected in series via four buses 21. That is, Figure 4 The battery pack 200 consists of five batteries connected in series. Although no example is shown, in a battery pack containing multiple individual cells electrically connected in parallel, for example, multiple negative terminals are connected to each other via a busbar, and multiple positive terminals are connected to each other via a busbar, so that multiple individual cells can be electrically connected.
[0129] The positive terminal 7 of at least one of the five individual cells 100a to 100e is electrically connected to the positive side lead 22 for external connection. In addition, the negative terminal 6 of at least one of the five individual cells 100a to 100e is electrically connected to the negative side lead 23 for external connection.
[0130] The battery pack according to the third embodiment includes the secondary battery according to the second embodiment. Therefore, it can exhibit high rate performance.
[0131] (Fourth implementation) According to a fourth embodiment, a battery pack is provided. This battery pack includes the battery pack according to the third embodiment. Alternatively, the battery pack may include a single secondary battery according to the second embodiment instead of the battery pack according to the third embodiment.
[0132] The battery pack may further include a protection circuit. This protection circuit controls the charging and discharging of the secondary battery. Alternatively, a circuit included in a device that uses the battery pack as a power source (e.g., electronic equipment, automobiles, etc.) may be used as the protection circuit for the battery pack.
[0133] Furthermore, the battery pack may also include external terminals for power supply. These external terminals are components used to output current from the secondary battery to the outside and / or to input current from the outside to the secondary battery. In other words, when the battery pack is used as a power source, current is supplied to the outside via the external terminals for power supply. Furthermore, when the battery pack is being charged, charging current (including regenerative energy from the power source of an automobile, etc.) is supplied to the battery pack via the external terminals for power supply.
[0134] Next, an example of the battery pack involved in the embodiment will be described with reference to the accompanying drawings.
[0135] Figure 5 This is an exploded perspective view that roughly represents an example of a battery pack. Figure 6 It means Figure 5 The diagram shows a block diagram of an example of the circuitry for the battery pack.
[0136] Figure 5 and Figure 6 The battery pack 300 shown includes a container 31, a cover 32, a protective sheet 33, a battery pack 200, a printed circuit board 34, wiring 35, and an insulating plate (not shown).
[0137] Figure 5 The container 31 shown is a square container with a rectangular base. The container 31 is configured to house the protective sheet 33, the battery pack 200, the printed circuit board 34, and the wiring 35. The cover 32 has a rectangular shape. The cover 32 houses the battery pack 200 and the like by covering the container 31. Although not shown, the container 31 and the cover 32 are provided with openings or connection terminals for connecting to external devices.
[0138] The battery pack 200 includes multiple individual cells 100, positive electrode side lead 22, negative electrode side lead 23, and adhesive tape 24.
[0139] At least one of the plurality of individual cells 100 is a secondary battery according to the second embodiment. Each of the plurality of individual cells 100 is as follows: Figure 6As shown, the individual cells 100 are electrically connected in series. Multiple individual cells 100 can also be connected in parallel, or a combination of series and parallel connections can be used. If multiple individual cells 100 are connected in parallel, the battery capacity increases compared to a series connection.
[0140] Adhesive tape 24 is used to bundle multiple individual cells 100 together. Alternatively, heat-shrinkable tape can be used to secure the multiple individual cells 100 instead of adhesive tape 24. In this case, protective sheets 33 are placed on both sides of the battery pack 200, and the heat-shrinkable tape is wrapped around the pack and then heat-shrinked to bundle the multiple individual cells 100 together.
[0141] One end of the positive electrode lead 22 is connected to the battery pack 200. One end of the positive electrode lead 22 is electrically connected to the positive electrode of one or more individual cells 100. One end of the negative electrode lead 23 is connected to the battery pack 200. One end of the negative electrode lead 23 is electrically connected to the negative electrode of one or more individual cells 100.
[0142] The printed circuit board 34 is disposed along one of the shorter sides of the inner surface of the receiving container 31. The printed circuit board 34 includes a positive-side connector 342, a negative-side connector 343, a thermistor 345, a protection circuit 346, wirings 342a and 343a, an external terminal 350 for power supply, positive-side wiring 348a, and negative-side wiring 348b. One main surface of the printed circuit board 34 faces one side of the battery pack 200. An insulating plate (not shown) is sandwiched between the printed circuit board 34 and the battery pack 200.
[0143] The other end 22a of the positive lead 22 is electrically connected to the positive connector 342. The other end 23a of the negative lead 23 is electrically connected to the negative connector 343.
[0144] A thermistor 345 is fixed to a main surface of a printed circuit board 34. The thermistor 345 detects the temperature of each individual cell 100 and sends its detection signal to a protection circuit 346.
[0145] An external terminal 350 for power supply is fixed to another main surface of the printed circuit board 34. The external terminal 350 for power supply is electrically connected to a device located outside the battery pack 300. The external terminal 350 for power supply includes a positive terminal 352 and a negative terminal 353.
[0146] The protection circuit 346 is fixed to another main surface of the printed circuit board 34. The protection circuit 346 is connected to the positive terminal 352 via a positive side wiring 348a. The protection circuit 346 is connected to the negative terminal 353 via a negative side wiring 348b. Furthermore, the protection circuit 346 is electrically connected to the positive connector 342 via wiring 342a. The protection circuit 346 is electrically connected to the negative connector 343 via wiring 343a. Moreover, the protection circuit 346 is electrically connected to each of the plurality of individual cells 100 via wiring 35.
[0147] The protective sheet 33 is disposed on the two inner sides of the receiving container 31 along the long side and on the inner side of the battery pack 200 opposite to the printed circuit board 34 along the short side. The protective sheet 33 is formed, for example, from resin or rubber.
[0148] The protection circuit 346 controls the charging and discharging of multiple individual batteries 100. In addition, based on the detection signal sent by the thermistor 345, or the detection signal sent by each individual battery 100 or battery pack 200, the protection circuit 346 disconnects the electrical connection between the protection circuit 346 and the external terminals 350 (positive terminal 352, negative terminal 353) for powering on external devices.
[0149] As a detection signal sent by the thermistor 345, examples include signals indicating that the temperature of a single cell 100 is above a predetermined temperature. As a detection signal sent by each single cell 100 or the battery pack 200, examples include signals indicating overcharging, over-discharging, and overcurrent of a single cell 100. In the case of detecting overcharging in each single cell 100, the battery voltage, or the positive or negative electrode potential, can be detected. In the latter case, a lithium electrode used as a reference electrode is inserted into each single cell 100.
[0150] It should be noted that the protection circuit 346 can also be a circuit included in a device that uses the battery pack 300 as a power source (e.g., electronic equipment, automobiles, etc.).
[0151] Furthermore, the battery pack 300, as described above, includes an external terminal 350 for power supply. Therefore, the battery pack 300 can output current from the battery pack 200 to an external device and input current from an external device into the battery pack 200 via the external terminal 350. In other words, when the battery pack 300 is used as a power source, current from the battery pack 200 is supplied to the external device via the external terminal 350. Furthermore, when the battery pack 300 is being charged, charging current from the external device is supplied to the battery pack 300 via the external terminal 350. When the battery pack 300 is used as a vehicle battery, the regenerative energy from the vehicle's power source can be utilized as the charging current from the external device.
[0152] It should be noted that the battery pack 300 may also include multiple battery groups 200. In this case, the multiple battery groups 200 may be connected in series, in parallel, or a combination of series and parallel connections. Furthermore, the printed circuit board 34 and wiring 35 may be omitted. In this case, the positive terminal lead 22 and the negative terminal lead 23 may be used as the positive terminal 352 and negative terminal 353 of the external terminal 350 for power supply, respectively.
[0153] Such battery packs are used, for example, in applications requiring excellent cycle performance when drawing high currents. Specifically, they are used as power sources for electronic devices, stationary batteries, and in-vehicle batteries for various vehicles. Examples of electronic devices include digital cameras. This battery pack is particularly suitable for use as an in-vehicle battery.
[0154] The battery pack according to the fourth embodiment includes the secondary battery according to the second embodiment or the battery pack according to the third embodiment. Therefore, it can exhibit high rate performance.
[0155] (Fifth implementation) According to a fifth embodiment, a vehicle is provided. This vehicle is equipped with the battery pack described in the fourth embodiment.
[0156] In the vehicle, the battery pack, for example, recovers regenerative energy from the vehicle's kinetic energy. The vehicle may also include a mechanism (Regenerator) that converts the vehicle's kinetic energy into regenerative energy.
[0157] Examples of vehicles include two- to four-wheeled hybrid electric vehicles, two- to four-wheeled electric vehicles, electric bicycles, and railway vehicles.
[0158] There are no particular restrictions on the location of the battery pack in a vehicle. For example, when mounting the battery pack in a car, it can be installed in the engine compartment, at the rear of the vehicle body, or under the seats.
[0159] The vehicle can also be equipped with multiple battery packs. In this case, the batteries in each battery pack can be electrically connected in series, in parallel, or a combination of series and parallel connections. For example, if each battery pack contains battery groups, the battery groups can be electrically connected in series, in parallel, or a combination of series and parallel connections. Alternatively, if each battery pack contains a single battery, the individual batteries can be electrically connected in series, in parallel, or a combination of series and parallel connections.
[0160] Next, an example of a vehicle involved in the implementation method will be described with reference to the accompanying drawings.
[0161] Figure 7 This is a partial perspective view that roughly represents an example of a vehicle.
[0162] Figure 7 The vehicle 400 shown includes a vehicle body 40 and a battery pack 300 as described in the fourth embodiment. Figure 7 In the example shown, vehicle 400 is a four-wheeled car.
[0163] The vehicle 400 can also be equipped with multiple battery packs 300. In this case, the batteries contained in the battery pack 300 (e.g., single cells or battery packs) can be connected in series, in parallel, or a combination of series and parallel connections.
[0164] exist Figure 7 The diagram illustrates an example where the battery pack 300 is mounted in the engine compartment located at the front of the vehicle body 40. As mentioned above, the battery pack 300 can also be mounted, for example, at the rear of the vehicle body 40 or under the seats. The battery pack 300 can be used as a power source for the vehicle 400. Furthermore, the battery pack 300 can recover regenerative energy from the power source of the vehicle 400.
[0165] Next, refer to Figure 8 The implementation method of the vehicle involved in the implementation method will be described.
[0166] Figure 8 This is a diagram that roughly represents an example of a control system for the electrical system in a vehicle. Figure 8 The vehicle 400 shown is an electric vehicle.
[0167] Figure 8 The vehicle 400 shown includes a vehicle body 40, a vehicle power supply 41, a vehicle ECU (Electric Control Unit) 42 which is a higher-level control device for the vehicle power supply 41, an external terminal (a terminal for connecting to an external power supply) 43, a converter 44, and a drive motor 45.
[0168] Vehicle 400 uses a power supply 41, for example, mounted in the engine compartment, at the rear of the vehicle body, or under the seats. It should be noted that... Figure 8 In the vehicle 400 shown, the mounting location of the vehicle power supply 41 is roughly indicated.
[0169] The vehicle power supply 41 includes multiple (e.g., three) battery packs 300a, 300b and 300c, a battery management unit (BMU) 411 and a communication bus 412.
[0170] Battery pack 300a includes battery pack 200a and battery pack monitoring device 301a (e.g., VTM: Voltage Temperature Monitoring). Battery pack 300b includes battery pack 200b and battery pack monitoring device 301b. Battery pack 300c includes battery pack 200c and battery pack monitoring device 301c. Battery packs 300a to 300c are the same type of battery pack as battery pack 300 described above, and battery packs 200a to 200c are the same type of battery pack as battery pack 200 described above. Battery packs 200a to 200c are electrically connected in series. Battery packs 300a, 300b, and 300c can be removed independently and can be exchanged with other battery packs 300.
[0171] Each of the battery packs 200a to 200c comprises a plurality of individual cells connected in series. At least one of the plurality of individual cells is a secondary battery according to the second embodiment. The battery packs 200a to 200c are charged and discharged via the positive terminal 413 and the negative terminal 414, respectively.
[0172] The battery management device 411 communicates with the battery pack monitoring devices 301a-301c, and collects information about voltage, temperature, etc., for each individual cell 100 included in the battery packs 200a-200c contained in the vehicle power supply 41. Thus, the battery management device 411 collects information regarding the maintenance of the vehicle power supply 41.
[0173] The battery management device 411 is connected to the battery monitoring devices 301a-301c via a communication bus 412. In the communication bus 412, one communication line has multiple nodes (the battery management device 411 and one or more battery monitoring devices 301a-301c). The communication bus 412 is, for example, a communication bus based on the CAN (Control Area Network) standard.
[0174] The battery monitoring devices 301a to 301c measure the voltage and temperature of each individual cell constituting the battery packs 200a to 200c based on instructions received from the battery management device 411 via communication. However, the temperature can be measured at multiple locations for only one battery pack, or the temperature of all individual cells can be measured.
[0175] The vehicle power supply 41 may also have an electromagnetic contactor (e.g., to switch the electrical connection between the positive terminal 413 and the negative terminal 414) to enable or disable the connection. Figure 8 The switching device 415 shown is included. The switching device 415 includes a pre-charge switch (not shown) that is turned on when charging the battery packs 200a-200c, and a main switch (not shown) that is turned on when supplying output from the battery packs 200a-200c to a load. Both the pre-charge switch and the main switch have relay circuits (not shown) that are switched on or off by signals supplied to coils located near the switching elements. The electromagnetic contactors, such as the switching device 415, are controlled based on control signals from the vehicle ECU 42 that control the operation of the battery management device 411 or the vehicle 400 as a whole.
[0176] The converter 44 converts the input DC voltage into a high-voltage 3-phase AC voltage for motor drive. The 3-phase output terminals of the converter 44 are connected to the 3-phase input terminals of each of the drive motors 45. The converter 44 is controlled based on control signals from the vehicle ECU 42 used to control the operation of the battery management device 411 or the vehicle as a whole. The output voltage from the converter 44 is adjusted by controlling the converter 44.
[0177] The drive motor 45 rotates by electricity supplied by the converter 44. The driving force generated by the rotation of the drive motor 45 is transmitted to the axle and drive wheel W, for example, through a differential gear unit.
[0178] Furthermore, although not shown, vehicle 400 is equipped with a regenerative braking mechanism (regenerator). When braking vehicle 400, the regenerative braking mechanism causes drive motor 45 to rotate, converting kinetic energy into regenerative energy as electrical energy. The regenerative energy recovered by the regenerative braking mechanism is input to converter 44, where it is converted into direct current. The converted direct current is input to vehicle power supply 41.
[0179] One terminal of the connecting line L1 is connected to the negative terminal 414 of the vehicle power supply 41. The other terminal of the connecting line L1 is connected to the negative input terminal 417 of the converter 44. A current detection unit (current detection circuit) 416 of the battery management device 411 is provided on the connecting line L1 between the negative terminal 414 and the negative input terminal 417.
[0180] A terminal of a connecting line L2 is connected to the positive terminal 413 of the vehicle power supply 41. The other terminal of the connecting line L2 is connected to the positive input terminal 418 of the converter 44. A switching device 415 is provided on the connecting line L2 between the positive terminal 413 and the positive input terminal 418.
[0181] External terminal 43 is connected to battery management device 411. External terminal 43 can be connected to an external power source, for example.
[0182] The vehicle ECU 42 responds to input from the driver and other operators, and coordinates with other management and control devices, including the battery management device 411, to control the vehicle power supply 41, switching device 415, and converter 44. Through the coordinated control of the vehicle ECU 42 and others, it controls the output of power from the vehicle power supply 41 and the charging of the vehicle power supply 41, thus managing the overall vehicle 400. Data related to the maintenance of the vehicle power supply 41, such as the remaining capacity of the vehicle power supply 41, is transmitted between the battery management device 411 and the vehicle ECU 42 via a communication line.
[0183] The vehicle according to the fifth embodiment is equipped with the battery pack according to the fourth embodiment. Therefore, a high-performance vehicle can be provided.
[0184] Example The following describes the embodiments.
[0185] (Example 1) A slurry was prepared by dispersing and mixing niobium titanium oxide (TiNb₂O₇) powder, carbon black, carbon nanotubes, carboxymethyl cellulose, and styrene-butadiene rubber (SBR) in an aqueous solvent at a weight ratio of 84:5:1:5:5. The properties of the carbon nanotubes used are shown in Table 1 below. A planetary mixer was used for dispersion. First, the components other than SBR were dispersed at 50 rpm for 120 minutes, and then SBR was added and dispersed at 20 rpm for 20 minutes to prepare the slurry.
[0186] Then, the above slurry is applied through a die at a coating amount of 100 g / m². 2 The coating is applied to both sides of the aluminum foil current collector. A 0.3mm thick gasket is used for the die head, and the coating is performed at a conveying speed of 5m / min. The coated slurry is allowed to dry, and the resulting laminate is then pressed.
[0187] Make electrodes by doing this.
[0188] (Example 2) For the replacement of active material with lithium titanate Li4Ti5O 12 Apart from this point, the electrodes are fabricated in the same manner as in Example 1.
[0189] (Example 3) Except for the substitution of titanium dioxide (TiO2) for the negative electrode active material, the electrode was fabricated in the same manner as in Example 1.
[0190] (Examples 4 and 5) As shown in Table 1, carbon nanotubes with different physical properties were used to fabricate the electrodes, except that the process was the same as in Example 1.
[0191] (Examples 6 and 7) The amount of carbon nanotubes added was varied as shown in Table 1, except that the electrodes were fabricated in the same manner as in Example 1.
[0192] (Example 8) After the slurry was dispersed, it was not immediately coated onto the current collector. After 30 days, the slurry was stirred again at 20 rpm for 5 minutes using a planetary mixer before being coated onto the current collector. Except for this, the electrode was fabricated in the same manner as in Example 1.
[0193] (Example 9) In the slurry coating process, the conveying speed of the aluminum foil current collector was changed to 10 m / min, and the electrode was fabricated in the same manner as in Example 1.
[0194] (Example 10) In the slurry coating process, the thickness of the gasket was changed to 0.1 mm, and the electrode was fabricated in the same manner as in Example 1.
[0195] (Comparative Example 1) The electrodes were fabricated in the same manner as in Example 1, except that no carbon nanotubes were added.
[0196] (Comparative Example 2) The amount of carbon nanotubes added was varied as shown in Table 1, except that the electrodes were fabricated in the same manner as in Example 1.
[0197] (Comparative Example 3) As shown in Table 1, carbon nanotubes with different physical properties were used to fabricate the electrodes, except that the process was the same as in Example 1.
[0198] (Comparative Example 4) In the slurry coating process, the conveying speed of the aluminum foil current collector was changed to 0.5 m / min, and the electrode was fabricated in the same manner as in Example 1.
[0199] Table 1 summarizes the electrode fabrication conditions for each example. Specifically, it shows the oxides used for the active material, the properties of the carbon nanotubes, the number of days from slurry dispersion to coating, the current collector transport speed during slurry coating, and the gasket thickness.
[0200] <Evaluation> For the electrodes obtained in the above examples, a 10 cm square region on the main surface of the layer containing the active material was photographed, and the image was analyzed using the method described above. For the obtained spectrum, a high-speed Fourier transform was performed to obtain the normalized amplitude at each frequency corresponding to a width of 1 mm–10 mm.
[0201] Next, a 10 cm square sample was cut out. The cut sample was placed on an insulating plate, and the surface potential of the electrode surface was measured using a surface potentiometer. Then, another 10 cm square sample was prepared. The two electrode samples were overlapped and clamped from both sides with Teflon plates (registered trademark), and vibrated for 60 seconds. Afterward, when the overlapping upper electrode sample was lifted, it was visually confirmed whether the lower electrode sample was lifted. If the lower sample was lifted, it was considered "present" electrostatic adsorption; if not, it was considered "absent".
[0202] Furthermore, after peeling one side of each of the two active material layers of the obtained electrode from the current collector, the remaining portion of the electrode is punched to a 14mm diameter. A spherical electrode was prepared by dissolving LiPF6 in a mixed solution of ethylene carbonate and diethyl carbonate. A 2032-type coin cell was fabricated using the obtained spherical electrode as the working electrode, metallic Li as the counter electrode, and the aforementioned liquid non-aqueous electrolyte as the electrolyte. Charging at 1C and discharging at 0.2C, as well as charging at 1C and discharging at 10C, were performed within a voltage range of 3.0 V–1.0 V. The discharge capacity was measured at each discharge stage. The capacity at 10C discharge relative to the capacity at 0.2C discharge was calculated as an indicator of the coin cell's discharge rate performance, and the 10C / 0.2C capacity ratio was determined.
[0203] The results of the above evaluations are shown in Table 2 below.
[0204] As shown in Table 2, for the electrodes fabricated in Examples 1 to 10, the brightness variation within a 1mm-10mm width period (1mm≤L(GV)≤10mm) determined by image analysis was 0.3 cd / m. 2 The amplitudes mentioned above indicate that, based on this, the brightness variations of the electrodes in Examples 1-10 exhibit periodicity. In contrast, the amplitudes of the brightness variations in the electrodes fabricated in Comparative Examples 1-4 are also less than 0.3 cd / m above the maximum value. 2 Therefore, it can be concluded that, for the electrodes of Comparative Examples 1 to 4, the changes in brightness did not exhibit periodicity.
[0205] Regarding the electrodes of Examples 1-10 and Comparative Example 2, the surface potential was low, and no electrostatic adsorption occurred. In contrast, the electrodes of Comparative Examples 1, 3, and 4 had high surface potentials, and electrostatic adsorption occurred. For the electrodes of Examples 1-10, it was found that the periodicity of the carbon distribution on the electrode surface could dissipate the charge on the electrode surface, thus preventing electrostatic adsorption. For the electrode of Comparative Example 2, it is speculated that although the carbon distribution was not periodic, electrostatic adsorption did not occur simply because of the large amount of conductive agent. For Comparative Example 1, it can be determined that the surface potential of the electrode became the highest due to the absence of a conductive agent, and electrostatic adsorption occurred due to the accumulation of charge. For Comparative Examples 3 and 4, it can be determined that although a conductive agent was moderately included, the lack of periodicity in the carbon distribution led to the accumulation of charge on the electrode surface, resulting in electrostatic adsorption.
[0206] The coin cells using electrodes from Examples 1-10 and Comparative Example 4, respectively, exhibited higher discharge rate performance compared to coin cells using electrodes from other examples. Regarding the coin cell using the electrode of Comparative Example 1, it was determined that the high battery resistance was due to the absence of a conductive agent. For the electrode of Comparative Example 2, it was determined that although the conductivity was high, the excessive conductive agent hindered the conduction of the electrolyte and lithium ions within the electrode. For Comparative Example 3, it was determined that although the same amount of carbon nanotubes as in Examples 1-10 were used as a conductive agent, the lack of a periodic distribution prevented the formation of conductive pathways along the electrode surface.
[0207] According to one or more embodiments and examples described above, an electrode having a layer containing active material can be provided. The layer containing active material contains oxide active material and fibrous carbon. The brightness of the main surface of the layer containing active material exhibits periodic changes in a specific direction. Batteries manufactured using this electrode have a high yield. Furthermore, this electrode can provide secondary batteries and battery packs with high rate performance, as well as vehicles incorporating the battery pack.
[0208] Several embodiments of the present invention have been described, but these embodiments are provided by way of example and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their variations are included in the scope and spirit of the invention, as well as in the invention described in the claims and its equivalents.
[0209] It should be noted that the above-described implementation methods can be summarized into the following technical solutions.
[0210] (Technical Solution 1) An electrode comprising a layer of active material containing oxide active material and fibrous carbon, The brightness of the main surface of the aforementioned layer containing active substances exhibits periodic variations in a specific direction.
[0211] (Technical Solution 2) According to Technical Solution 1 above, when the period of the brightness variation is set to L (GV), the periodic change of brightness in the specific direction on the main surface of the layer containing the active material has an amplitude of 0.3 cd / m in the range of 1 mm ≤ L (GV) ≤ 10 mm. 2 The above cycles.
[0212] (Technical Solution 3) According to the above technical solution 1 or 2, the above fibrous carbon has a fiber length of more than 10 μm and less than 100 μm.
[0213] (Technical Solution 4) According to the above technical solutions 1 to 3, the above oxide active material includes titanium oxide.
[0214] (Technical Solution 5) A secondary battery, comprising: positive electrode, Negative electrode, and Electrolytes, The aforementioned negative electrode is the electrode described in any one of the above technical solutions 1 to 4.
[0215] (Technical Solution 6) A battery pack comprising the secondary battery described in Technical Solution 5 above.
[0216] (Technical Solution 7) According to the above technical solution 6, it further comprises: External terminals for power supply, and Protection circuit.
[0217] (Technical Solution 8) According to the above-mentioned technical solution 6 or 7, it comprises multiple of the above-mentioned secondary batteries. The aforementioned secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel connections.
[0218] (Technical Solution 9) A vehicle equipped with a battery pack as described in any one of the above-mentioned technical solutions 6 to 8.
[0219] (Technical Solution 10) The vehicle according to the above technical solution 9 includes a mechanism for converting the kinetic energy of the vehicle into regenerative energy.
Claims
1. An electrode comprising a layer of active material containing an oxide active material and fibrous carbon, The brightness of the main surface of the layer containing the active material exhibits periodic variations in a specific direction.
2. The electrode according to claim 1, wherein, When the period of brightness variation is set to L (GV), the periodic change of brightness in the specific direction on the main surface of the layer containing the active material has an amplitude of 0.3 cd / m in the range of 1 mm ≤ L (GV) ≤ 10 mm. 2 The above cycles.
3. The electrode according to claim 1 or 2, wherein, The fibrous carbon has a fiber length of more than 10 μm and less than 100 μm.
4. The electrode according to claim 1 or 2, wherein, The oxide active material includes titanium oxide.
5. A secondary battery, comprising: positive electrode, Negative electrode, and Electrolytes, The negative electrode is the electrode according to claim 1 or 2.
6. A battery pack comprising the secondary battery of claim 5.
7. The battery pack according to claim 6, wherein, Further features include: External terminals for power supply, and Protection circuit.
8. The battery pack according to claim 6, wherein, Equipped with multiple of the aforementioned secondary batteries, The secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel connections.
9. A vehicle equipped with the battery pack of claim 6.
10. The vehicle according to claim 9, wherein, It includes a mechanism for converting the kinetic energy of the vehicle into regenerative energy.